Internalization of Local Culture In Student Management to Create a Superior Generation - Yuliyanna, Yuliyanna; Muhaeminah, Ummu; Awaliah S, Nurul Rezki; Alwi, Muhammad (Peneliti.net, 2024)
This study aims to investigate the influence of implementing the local 3S culture (Sipakatau, Sipakainge, and Sipakalebbi) in student management on shaping a superior generation in Indonesia. Through a literature review method, this research explores the concept of local culture as an approach to understanding how traditional values can be applied in the context of student management to create an excellent generation. The results highlight that the internalization of local culture in student management can create an inclusive and supportive learning environment, shaping students' character with integrity, hard work, cooperation, empathy, and respect for differences. By integrating local cultural values into education, the future generation can be developed into individuals who are not only academically superior but also possess a positive attitude, responsibility, and readiness to face the complexities of the future world. Therefore, student management that applies the legacy of local culture can be the key to shaping a superior generation ready to face global challenges with a positive and integrity-driven attitude.